1997
DOI: 10.1051/parasite/1997043203
|View full text |Cite
|
Sign up to set email alerts
|

Lectins (hemagglutinins) in the gut of the important disease vectors

Abstract: Summary :The review is devoted to the gut lectins/hemagglutinins of the following representatives of important disease vectors : ticks, kissing-bugs, mosquitoes, sandflies and tsetse flies. The paper surveys the recent knowledge on these carbohydrate binding factors with respect to their structural and functional properties, and their significance for pathogen/parasite transmission by the blood-sucking arthropods. Recent results suggest that in most vectors the gut lectin activities are blood-meal enhanced, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Lectins have been extensively studied in invertebrates with the best known invertebrate lectins from the horseshoe crabs and scorpions (Olafsen, 1986(Olafsen, , 1996Vasta and Marchalonis, 1984). Studies on tick lectins have been extensively reviewed by Grubhoffer et al (1997Grubhoffer et al ( , 2004 and thus are only briefly discussed in this paper.…”
Section: Hemagglutinationmentioning
confidence: 99%
“…Lectins have been extensively studied in invertebrates with the best known invertebrate lectins from the horseshoe crabs and scorpions (Olafsen, 1986(Olafsen, , 1996Vasta and Marchalonis, 1984). Studies on tick lectins have been extensively reviewed by Grubhoffer et al (1997Grubhoffer et al ( , 2004 and thus are only briefly discussed in this paper.…”
Section: Hemagglutinationmentioning
confidence: 99%
“…In vectors of infectious diseases lectins have a regulatory role in the refractoriness/susceptibility to transmitted trypanosomatid parasites (for review see Welburn and Maudlin 1999). Studies carried out on various sandfly species demonstrated the presence of gut lectin activity specific for aminosugars and heparin (for review see Grubhoffer et al 1997). The activity theoretically serves as one of factors affecting sandfly susceptibility to Leishmania infections (Volf et al 1998); however, no information is available about its role in bacterial infections.…”
mentioning
confidence: 99%
“…If so, then those interactions may function as reciprocal ones, where tissue-specific tick lectins may enter counterpart interactions equally as lectins of LB spirochetes. Carbohydrate/glycan moieties of the membrane-bound or soluble proteins in tick tissues may serve as receptors of those lectin molecules (Grubhoffer et al 1997). Based on published results, a binding affinity to sialic acid and their derivatives or steric analogs has been revealed as a common feature of tissue-specific tick lectins.…”
Section: Resultsmentioning
confidence: 99%